Mixed neuroendocrine–non-neuroendocrine neoplasm of the ampulla of Vater: a case report - Kenjiro Date; Takaaki Tatsuguchi; Yuzo Shimokawa; Yusuke Niina; Daichi Kitahara; Hirotaka Kuga; Sadafumi Tamiya; Kazuyoshi Nishihara; Toru Nakano (Surgical Case Reports)
Abstract Background Mixed neuroendocrine–non-neuroendocrine neoplasms of the ampulla of Vater are rare and heterogenous, making it difficult to achieve a definitive preoperative diagnosis. Herein, we describe a patient in whom a provisional diagnosis of mixed neuroendocrine–non-neuroendocrine neoplasm of the ampulla of Vater was made preoperatively. Case presentation Computed tomography revealed an enhancing periampullary tumor in a 69-year-old man with obstructive jaundice. Subsequent duodenoscopy revealed an ulcerated lesion in the swollen ampulla of Vater, from which six biopsies were collected. Pathological examination revealed adenocarcinoma in five of them. The remaining one was a neuroendocrine neoplasm according to immunohistochemical analysis. With a provisional diagnosis of mixed neuroendocrine–non-neuroendocrine neoplasm of the ampulla of Vater, the patient underwent subtotal stomach-preserving pancreaticoduodenectomy with modified Child’s reconstruction and was discharged without complications. Pathological examination revealed both adenocarcinoma and neuroendocrine carcinomas, each accounting for ≥ 30% of the tumor, resulting in a definitive diagnosis of mixed neuroendocrine–non-neuroendocrine neoplasm of the ampulla of Vater. Lymph node metastases with neuroendocrine components were also observed. Adjuvant chemotherapy was not administered because of the patient’s renal dysfunction. Liver and lymph node metastases were detected 2 months after surgery, the neuroendocrine component being considered responsible for that relapse. The patient underwent platinum-based chemotherapy at 50% dosage, which initially resulted in significant tumor shrinkage; however, he died 6 months after surgery. Conclusions While these tumors’ heterogeneity make definitive preoperative diagnosis of mixed neuroendocrine–non-neuroendocrine neoplasm of the ampulla of Vater difficult, the possibility of this disease can be considered by careful examination. Further study is needed to establish the optimal diagnostic criteria and treatment strategy.